On the Reproduction Ratio of Dengue Incidence in Semarang, Indonesia 2015-2018 - Puspita, Juni Wijayanti; Fakhruddin, Muhammad; Fahlena, Hilda; Rohim, Fatkhur; Sutimin, Sutimin (Indonesian Bio-Mathematical Society, 2019)
Dengue is one of the mosquito-borne diseases caused by dengue viruses (DENV), which has become endemic in most tropical and subtropical countries, including Indonesia. Since there is a lot of dengue incidence on children of age less than fourteen years old in Semarang, Indonesia, it is the interest here to analyze the different rates of infection among different age groups. A SIR-UV mathematical model with age structure in human the population is constructed to describe dengue transmission in Semarang from 2015 to 2018. In this study, we separated the human population into four age classes: children (0-4 years), youngster (5-14 years), productive adults (15-60 years) and non-productive adults (over 60 years). We use Particle Swarm Optimization to obtain optimal parameters for the transmission rates based on the yearly incidence. The basic reproduction ratio (R0) is derived from the Next Generation Matrix and is evaluated by using the optimal parameters for data Semarang in 2015-2018. Numerical simulation results show that the number of dengue incidence is in a good agreement with the actual data in Semarang for 2015-2018.